A Systematic Mapping Study of the Onboarding Process in Software Development Organizations - Perpétua, Sueli Pereira; Vieira, Sávio Luiz; Portela, Carlos dos Santos; Souza, Maurício Ronny de Almeida (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
The onboarding process refers to the organizational integration or socialization of new employees to the company and their role. This includes training, orientation, support, and communication, seeking to help newcomers to adapt to the new culture and work environment. Since software development is a human activity that requires collaboration and teamwork, especially in the professional environment, onboarding is a critical process to ensure the proper integration of new employees in software projects. Thus, this paper aims to identify the main approaches, practices, trends, and challenges related to the onboarding process in the Software Engineering context. We conducted a Systematic Mapping Study, which resulted in the selection of 23 primary studies. The main findings include the observation that onboarding process is context-sensitive, affected by characterisctics such as organization size, work model, and development methodologies. We also found that there is a lack of studies evaluating models and tools. Finally, there is a heavy focus on oboarding activities related to learning and socialization, in contrast to developing the confidence of newcomers.